Roles of Non-coding RNAs in Central Nervous System Axon Regeneration - Li, Pei; Jia, Yuanyuan; Tang, Wenbo; Cui, Qingjun; Liu, Ming; Jiang, Jingjing (Frontiers in Neuroscience, 2021)
Axons in the central nervous system often fail to regenerate after injury due to the limited intrinsic regeneration ability of the central nervous system (CNS) and complex extracellular inhibitory factors. Therefore, it is of vital importance to have a better understanding of potential methods to promote the regeneration capability of injured nerves. Evidence has shown that non-coding RNAs play an essential role in nerve regeneration, especially long non-coding RNA (lncRNA), microRNA (miRNA), and circular RNA (circRNA). In this review, we profile their separate roles in axon regeneration after CNS injuries, such as spinal cord injury (SCI) and optic nerve injury. In addition, we also reveal the interactive networks among non-coding RNAs.